2009
DOI: 10.3852/07-202
|View full text |Cite
|
Sign up to set email alerts
|

A multilocus phylogeny of theMetarhizium anisopliaelineage

Abstract: Metarhizium anisopliae, the type species of the anamorph entomopathogenic genus Metarhizium, is currently composed of four varieties, including the type variety, and had been demonstrated to be closely related to M. taii, M. pingshaense and M. guizhouense. In this study we evaluate phylogenetic relationships within the M. anisopliae complex, identify monophyletic lineages and clarify the species taxonomy. To this end we have employed a multigene phylogenetic approach using near-complete sequences from nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
452
0
32

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 552 publications
(517 citation statements)
references
References 49 publications
14
452
0
32
Order By: Relevance
“…In eastern Canada, Mb was associated with the rhizosphere soil of trees rather than with the rhizospheres of plants in open fields (Wyrebek et al 2011), indicating the association of Mb with forested habitat. Furthermore, the cold-active and forest-dominant genotypic group of M. anisopliae sensu lato had been reported in the same area (Bidochka et al 2001), which partially corresponds to Mb (Bischoff et al 2009). Accordingly, Mb in Canada and Japan seem to have similar habitat and temperature preferences.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In eastern Canada, Mb was associated with the rhizosphere soil of trees rather than with the rhizospheres of plants in open fields (Wyrebek et al 2011), indicating the association of Mb with forested habitat. Furthermore, the cold-active and forest-dominant genotypic group of M. anisopliae sensu lato had been reported in the same area (Bidochka et al 2001), which partially corresponds to Mb (Bischoff et al 2009). Accordingly, Mb in Canada and Japan seem to have similar habitat and temperature preferences.…”
Section: Discussionmentioning
confidence: 83%
“…M. anisopliae s. l. is known to be a complex of cryptic species which are now classified by a molecular phylogenetic approach and can be distinguished by DNA sequences (Bischoff et al 2009). Bidochka et al (2001) demonstrated that cryptic species of M. anisopliae s. l. were associated with specific habitat type preferences rather than host insects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ITS (Internal Transcribed Spacer) sequences have been widely accepted and promoted as a supposedly universal DNA “barcode” and, indeed, have adequately differentiated a huge variety of fungi. Nonetheless, it must be noted that for the Hypocreales – and especially for cordycipitoid entomopathogenic taxa – ITS has proven to have little to no taxonomic value (Driver et al 2000; Bischoff et al 2009). ITS sequences were excluded altogether from the analyses providing the new phylogenetic reclassifications of the genera Beauveria and Metarhizium as well as of the families Clavicipitaceae and Ophiocordycipitaceae (Rehner et al 2011; Kepler et al 2014; Quandt et al 2014).…”
Section: Using Genomic Databases: Are the Data Trustworthy Or Not?mentioning
confidence: 99%
“…Neither, of course, had the phylogenetically based reclassifications of species in these two genera (Bischoff et al 2009; Rehner et al 2011; Kepler et al 2014) yet happened, with their corresponding fragmentations of the well-recognised but morphologically defined species into multiple phylogenetically defined ones … and automatically placing some quotation marks around the base taxa in what we now know retrospectively to be major species complexes. During that symposium, I expressed hope that the next entomopathogenic fungus to be sequenced after these two critically important taxa would be Cordyceps militaris .…”
mentioning
confidence: 99%